Read into the lines: the positive effects of queues. Issue 5 (7th August 2018) - Tu, Rungting; Feng, Wenting; Lin, Cheryl; Tu, Pikuei
Abstract : Purpose: Companies work hard to reduce queue lengths due to the common belief that queues in general are undesirable. Extant literature mainly has focused on the negative consequences of queues and overlooked the potential positive effects. The purpose of this paper is to address the benefits of queues by examining how consumers of different segments may read into the lines (queues) as well as why and when positive effects occur. Design/methodology/approach: Applying and integrating psychology and marketing theories, the study develops a model with several propositions to identify and explain the mechanism and conditions under which queues have positive effects. Findings: Contrary to conventional belief, queues may serve as positive signs. In certain segments, consumers can perceive a queue as a reflection of superior service/product quality, an opportunity to fulfill the need(s) for self-uniqueness or social inclusion or an avenue to avoid social exclusion. In addition, the benefits of long queues may come from consumers' joining a line to seek desirable outcomes/gains based on their attribution of the queue, and consumers' prefactual thinking that regards "not joining" the queue as potential losses. Furthermore, the magnitude of such effects depends on queue distinctiveness, choice heterogeneity, consumption hedonism and performance uncertainty. Originality/value: This paper explains how, why and when a long queue can be read as positive cues and benefits both the firms and target/potential consumers. The authors demonstrate the psychological mechanisms of joining a queue based on attribution and prefactual thinking, and identify conditions under which positive queue effects are most likely to occur.